Sedimentation in the Rupnarayan River Volume 2: Estuarine Environment of Deposition - Kumar Maity, Swapan (SpringerBriefs in Earth Sciences,, 2018)
This book elucidates sedimentation processes at work in the Rupnarayan River, with particular focus on the environment of sediment deposition under a tidal system. It addresses the various complexities arising from the interactions between riverine and marine processes, as well as the seasonal fluctuations in available and critical shear stress that lead to sedimentation. Logical explanations of the research findings will help readers understand the mechanisms of sedimentation and both the sources and distributional patterns of sediments in estuarine environments. The book offers a valuable guide and faithful companion for all students and researchers working on fluvial geomorphology and sedimentology, as well as engineers, hydrologists, planners and other authorities interested in sedimentation and associated problems.